Pelatihan Sistem Akuntansi Koperasi Berbasis Web di Srikandi Jaya Sambas - Muji Burrohman; Herjiden Herjiden; Sisko Sisko; Ergus Ergus; Ridho Maulana; Komarudin Komarudin (Penerbit Goodwood, 2026)
Purpose: This community service program aims to enhance the digital financial literacy and accounting management skills of the members and administrators of Koperasi Produsen Srikandi Jaya Sambas in West Kalimantan through the implementation of a web-based accounting information system called Aplikasi Akuntansi Koperasi (AKSI). The initiative was developed in response to the cooperative’s limited financial management capacity and the absence of standardized accounting practices that align with modern digital governance principles. Methodology/Approach: The program was carried out at the cooperative’s office in Desa Sendoyan, Sambas Regency, by lecturers and students from Politeknik Negeri Sambas (Poltesa). A case-based learning and hands-on mentoring approach was applied, allowing participants to learn directly using real cooperative financial data. The AKSI system was designed in accordance with SAK EP and Permenkop No. 2/2024 standards and included stages such as installation, user registration, transaction recording, and automated financial reporting. Results: The implementation of the AKSI system significantly improved participants’ technical competence and digital accounting understanding, increasing from 52.60% to 90.91%. Participants reported higher confidence in performing transaction recording and generating financial statements. The system effectively produced accurate, real-time, and standardized reports, thereby improving efficiency, transparency, and accountability in cooperative financial management. Conclusions: The AKSI application enhanced efficiency, accuracy, and transparency in cooperative financial management. Limitations: The short duration of the program and the varying levels of digital literacy among participants may limit long-term sustainability. Contributions: This project contributes a replicable digital accounting model that supports cooperative modernization and promotes inclusive financial transparency across Indonesia.